Pre- and postoperative evaluation by photoplethysmography in patients receiving surgery for lower-limb varicose veins - Saliba Júnior, Orlando Adas [UNESP]; Giannini, Mariangela [UNESP]; Mórbio, Ana Paula; Saliba, Orlando [UNESP]; Rollo, Hamilton Almeida [UNESP] (International Journal Of Vascular Medicine, 2014)
Objective. To evaluate the effectiveness of surgery in treating primary varicose veins in the lower limbs by photoplethysmography (PPG) and duplex mapping (DM). Method. Forty-eight lower limbs were clinically evaluated according to the CEAP classification system and subjected to PPG and DM exams. Each limb had a venous refill time (VRT) of <20 seconds and a normal deep vein system (DVS) by DM. Results. The mean pre- and postoperative VRTs were 13.79 and 26.43 seconds, respectively (P < 0.0001). After surgery, 42 limbs (87.50%) had normal results by PPG (VRT > 20 seconds). Four limbs (8.33%) showed improved VRTs, but the VRTs did not reach 20 seconds. In the 2 limbs (4.17%) that maintained their original VRTs, the DM exams showed the presence of insufficient perforating veins. Conclusion. In most cases, PPG allows for a satisfactory evaluation of the outcome of varicose vein surgery.